Mimicking a honeybee queen?Vespa affinis indosinensis pérez 1910 hunts drones of Apis cerana f. 1793 - Koeniger, Nikolaus; Koeniger, Gudrun; Mardan, Makhdzir (1994)
Hornets (Vespa affinis) flying in a drone congregation area attracted drones of Apis cerana. The drones followed the hornet and were ‘manoeuvred’ towards a leaf or a tree. The hornet then rushed at one of the drones. Many attempts by the hornet to catch a drone were unsuccessful and all drones fled. After failing, the hornet returned to centre of the drone congregation area and repeated the behaviour. Only after successfully seizing of a drone did the hornet leave the drone congregation area carrying its prey. In a two‐choice test in the centre of the drone congregation area, free‐flying A. cerana drones preferred a hornet model to a live A. cerana queen. V. affinis apparently ‘exploits’ the intraspecific communication between queen and drones of A. cerana. Hunting of drones in the drone congregation area by V. affinis may be an example of predatory mimicry. 1994 Blackwell Verlag GmbH